If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 66 = 4t + -15t Combine like terms: 4t + -15t = -11t 66 = -11t Solving 66 = -11t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '11t' to each side of the equation. 66 + 11t = -11t + 11t Combine like terms: -11t + 11t = 0 66 + 11t = 0 Add '-66' to each side of the equation. 66 + -66 + 11t = 0 + -66 Combine like terms: 66 + -66 = 0 0 + 11t = 0 + -66 11t = 0 + -66 Combine like terms: 0 + -66 = -66 11t = -66 Divide each side by '11'. t = -6 Simplifying t = -6
| 2(6v-3)=-66 | | 2=x+4+x | | -2x-4+3=9 | | m-5m=-8 | | 84=7(v-79) | | -9+p/2=-12 | | 6+4x=6x-9 | | -7x+9=4x+141 | | 30y+20-3=7 | | 3x-1=-4x+6 | | 8y-4-5=5 | | 2/3(1/2) | | -2+x+7x=-50 | | -w-(3x-3w)+x= | | 3x+1+3x=-53 | | -3=1/3k | | -2u+6=-10 | | t/2-1=2 | | h-90/4=-2 | | -2=h-90/4 | | k-81/8=2 | | -13+8c=27 | | 2v+18=46 | | 2(v-40)=88 | | q/3-(-4)=7 | | 2=3n-1 | | n/2-14=-11 | | 7(-8-7x)=-56 | | 3+2m=-3 | | x/0.07-x | | f/4-6=-2 | | 7x-3(-x-6)=-32 |